Effects of exergames in children at risk and significant movement difficulty: a blinded randomized study Efeitos dos exergames em crianças com risco e dificuldade significativa de movimento: um estudo cego randomizado - Libardoni dos Santos J.O. (2018)
© 2018 Colégio Brasileiro de Ciências do EsporteThe aimed of this study was to verify the effect of a motor intervention program with exergames in children with risk and significant movement difficulty. 18 sessions of 45 minutes were performed. The MABC‐2 battery was used to identify children at risk and motor difficulty. In the pre‐test, in the experimental group there were two children with difficulty of movement and four children with indicative of risk of difficulty, in the post‐test analyzes, it was verified that only two children were at risk of difficulty and four were without difficulty of Movement. With this, it is suggested that the exergames can be useful tools for the improvement of the motor performance, besides offering subsidy for an alternative of stimulation of the movement.